Current Theories and Clinical Trial Evidence for Limiting Human Abdominal Aortic Aneurysm Growth - Yu, Jing; Liu, Shuai; Huang, Jianhua; Wang, Wei (Current Drug Targets, 2018)
Background: Abdominal aortic aneurysm (AAA) refers to localized dilation of abdominal aorta. AAA is largely asymptomatic, but aneurysmal rupture results in a high mortality rate. AAA with a diameter greater than 55 mm carries a high risk of rupture. There are currently no known medical treatments effective in limiting the growth of small AAA. Objective: To review the current status of and challenges faced in limiting AAA growth. Methods: Data from human investigations and animal model studies were summarized. In particular, the ClinicalTrials.gov website was searched for details of ongoing or completed studies related to AAA growth. We searched the key words ‘abdominal aortic aneurysm’ and ‘drugs’ to identify potential target drugs for slowing or stopping AAA growth. Results: These clinical trials involve a number of challenges, including demonstrating the design of the trial, minimizing the participant dropout rate, and developing accurate outcome assessments during the trials. A number of clinical trials have concentrated on pharmaceutical intervention (such as angiotensin- converting enzyme inhibitors, beta-blockers, statins, and antibiotics) that could be effective for AAA patients in delaying or reversing aneurysm expansion and postponing the endpoint for elective surgical repair. Conclusions: Further randomized, controlled, clinical trials are required to develop effective nonsurgical therapies for AAA.
Keywords: atorvastatin